The pandemic period length modelled through queue systems - Ferreira, M. (2022)
Despite the huge progress in infectious diseases control worldwide, still epidemics happen, being the annual influenza outbreaks examples of those occurrences. To have a forecast for the epidemic period length is very important because, in this period, it is necessary to strengthen the health care. With more reason, this happens with the pandemic period, since the pandemic is an epidemic with a great population and geographical dissemination. Predominantly using results on the M\G\infinity queue busy period, it is presented an application of this queue system to the pandemic period's parameters and distribution function study. The choice of the M\G\infinity queue for this model is adequate, with great probability, since the greatest is the number of contagions the greatest the possibility of the hypothesis that they occur according to a Poisson process.